2023
DOI: 10.1186/s12885-023-11153-1
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib/II study of galunisertib in combination with nivolumab in solid tumors and non-small cell lung cancer

Abstract: Background In this phase Ib/II open-label study, tumor immune suppression was targeted in patients with advanced refractory solid tumors and patients with recurrent/refractory non-small cell lung cancer (NSCLC) using galunisertib with nivolumab. Methods Eligible patients were ≥ 18 years old, had an Eastern Cooperative Oncology Group performance status ≤ 1, and were treatment-naive for anti-programmed cell death-1, its ligand, or transforming growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Using galunisertib and the clinical anti-GD2 antibody dinutuximab, we showed that dual treatment could demonstrate dramatic reduction in tumour volume and metastatic burden by unleashing the ADCC capacity of NK cells in vivo . Our work highlights the importance of clinical trials such as NCT02423343 , 42 which has already shown promising patient outcomes for therapeutic antibodies and galunisertib dual therapy in solid tumours including lung cancer, and serve as rational for future considerations of this approach for malignant bladder cancers.…”
Section: Discussionmentioning
confidence: 94%
“…Using galunisertib and the clinical anti-GD2 antibody dinutuximab, we showed that dual treatment could demonstrate dramatic reduction in tumour volume and metastatic burden by unleashing the ADCC capacity of NK cells in vivo . Our work highlights the importance of clinical trials such as NCT02423343 , 42 which has already shown promising patient outcomes for therapeutic antibodies and galunisertib dual therapy in solid tumours including lung cancer, and serve as rational for future considerations of this approach for malignant bladder cancers.…”
Section: Discussionmentioning
confidence: 94%
“…In another phase II clinical trial, the combination of galunisertib and neoadjuvant chemoradiotherapy was well tolerated and was shown to increase the complete response rate to 32% in patients with locally advanced rectal cancer ( NCT02688712 ) 71 , thus advocating further evaluation in larger randomized clinical trials. The results of a phase Ib/II study of galunisertib combined with nivolumab in NSCLC showed that the combination was well tolerated and observed in a subset of patients in stage II NSCLC to the initial effect ( NCT02423343 ) 72 . In another phase II study of patients with recurrent glioblastoma, galunisertib in combination with lomustine failed to demonstrate an improvement in OS over lomustine alone ( NCT01582269 ) 73 .…”
Section: Small-molecule Agents Targeting Cytokine and Chemokine Pathwaysmentioning
confidence: 99%
“…However, the phase II cohort, which included only one patient with HCC, showed a PFS of 5.4 months and an OS of 14.5 months. Hence, comprehensive efficacy results for the use of nivolumab and galunisertib in HCC patients are yet to be determined [339].…”
Section: Therapeutic Vaccination Strategies In the Setting Of Hccmentioning
confidence: 99%